Application of Black Scholes Method to Determining Premium Insurance In the Potato Agricultural Based on Price Index - Sutisna, Sarah; Sukono, Sukono; Napitupulu, Herlina (iora, 2023)
Potato is one of the leading horticultural commodities. Potato farming business often experiences price fluctuations that cause losses to farmers.The government is making efforts to minimize the farmers' losses by issuing agricultural insurance programs. This study aims to determine the relationship between potato prices at the provincial level and potato prices at the farmer level and to determine agricultural insurance premiums based on the price index. The data used are potato price data at the West Java Province level and potato price data at the farmer level in Pangalengan District. The correlation between provincial level prices and farmer level prices can be obtained using the Pearson Product Moment correlation method. The price index is calculated using the relative price index method. Determination of the premium to be paid by farmers using the Black-Scholes method. The results of the analysis show that potato prices at the West Java Province level have a very strong correlation with farmer prices in Pangalengan District in October. Based on the Black-Scholes method, the premium value depends on the trigger value obtained with a price range between IDR 9,806,100.00 to IDR 10,267,784.00 for a sum insured of IDR 39,403,000 per one contract period. Various premium values can be a consideration for farmers in choosing an agricultural insurance policy.